Development and validation of a QuEChERS-UPLC-MS/MS method for multi-class pesticide residue analysis in dairy products - Lu, Zhou; Junpeng, Zhao; Kwesi Ketemepi, Hilary (CYTA: journal of food, 2025)
A QuEChERS-UPLC-MS/MS method was developed and validated for simultaneous determination of six pesticides (chlorpyrifos, malathion, carbofuran, thiodicarb, deltamethrin, and lambda-cyhalothrin) in dairy products. Samples (n=50), collected from a supermarket in Chongqing, China, were extracted with 1% acetic acid–acetonitrile, purified using PSA, and quantified by external-standard UPLC-MS/MS. All pesticides showed excellent linearity (0.001–0.50 mg/L, R² > 0.99), with LOQs of 0.002 mg/kg. Average recoveries at four spiking levels (0.002, 0.01, 0.1, 1.0 mg/kg) ranged from 89% to 110% (RSD 0.5–9.5%, n=5). Analysis of real samples revealed residues below China’s MRLs (GB 2763–2021), confirming regulatory compliance. The method meets analytical requirements for dairy matrices and offers a reliable framework adaptable to other international standards.